TAM-ing the CIA—Tumor-Associated Macrophages and Their Potential Role in Unintended Side Effects of Therapeutics for Cancer-Induced Anemia - Weiler, Stefan; Nairz, Manfred (Frontiers in Oncology, 2021)
Cancer-induced anemia (CIA) is a common consequence of neoplasia and has a multifactorial pathophysiology. The immune response and tumor treatment, both intended to primarily target malignant cells, also affect erythropoiesis in the bone marrow. In parallel, immune activation inevitably induces the iron-regulatory hormone hepcidin to direct iron fluxes away from erythroid progenitors and into compartments of the mononuclear phagocyte system. Moreover, many inflammatory mediators inhibit the synthesis of erythropoietin, which is essential for stimulation and differentiation of erythroid progenitor cells to mature cells ready for release into the blood stream. These pathophysiological hallmarks of CIA imply that the bone marrow is not only deprived of iron as nutrient but also of erythropoietin as central growth factor for erythropoiesis. Tumor-associated macrophages (TAM) are present in the tumor microenvironment and display altered immune and iron phenotypes. On the one hand, their functions are altered by adjacent tumor cells so that they promote rather than inhibit the growth of malignant cells. As consequences, TAM may deliver iron to tumor cells and produce reduced amounts of cytotoxic mediators. Furthermore, their ability to stimulate adaptive anti-tumor immune responses is severely compromised. On the other hand, TAM are potential off-targets of therapeutic interventions against CIA. Red blood cell transfusions, intravenous iron preparations, erythropoiesis-stimulating agents and novel treatment options for CIA may interfere with TAM function and thus exhibit secondary effects on the underlying malignancy. In this Hypothesis & Theory, we summarize the pathophysiological hallmarks, clinical implications and treatment strategies for CIA. Focusing on TAM, we speculate on the potential intended and unintended effects that therapeutic options for CIA may have on the innate immune response and, consequently, on the course of the underlying malignancy.